The Relationship between Domestic Violence, Social Support, and Self Esteem Women Victims - Atin Sumiarti; Herien Puspitawati (Journal of Family Sciences, 2017)
Domestic violence is action commit by a person to harm a family member. This study aimed to analyze the relationship between domestic violence, social support with self esteem of women as a victims. The sampel were 31 women victims of domestic violence in Bogor, West Java. Sampels were selected by purposive sampling, considering that the sampel had experienced domestic violence by her husband. The result showed that there was a negative correlation between age sampel with domestic violence. In addition, the results found showed a significant positive relationship between the length of education with social support and there is also a significant positive relationship between domestic violence with self esteem of this wife